Exploring sustainability reporting in Italian listed SMEs - Roberto, Fabiana; Principale, Salvatore; Carello, Luigi Andrea; Conte, Paolo (Piccola Impresa / Small Business, 2024)
Purpose: The Corporate Sustainability Reporting Directive (CSRD) requires European listed small and medium-sized enterprises (SMEs) to report environmental, social, and governance (ESG) information starting from 2028. The research aims to explore the extent of sustainability reporting in Italian listed SMEs and to evaluate the determinants that may have influenced the level of disclosure. Design/methodology/approach: An OLS regression was conducted on 65 GRI-based sustainability reports of Italian listed SMEs to assess determinant of the level of ESG disclosure. Findings: The study found that most of the analyzed reports inadequately documented information at the indicator level, with limited improvement in less substantial areas such as social and local community-related disclosures. The findings highlight the need for Italian SMEs to enhance the quality and completeness of their sustainability reporting to meet emerging regulatory requirements and societal expectations. Moreover, the size and sector could be determining factors that influenced the level of disclosure. Practical and Social Implication: This study contributes to understanding SMEs’ sustainability reporting practices within the context of evolving standards and regulations.